The palynology of the Lower Permian (Asselian-?Artinskian) Copacabana Formation of Apillapampa, Cochabamba, Bolivia - Di Pasquo Lartigue, Maria (2012)
The palynostratigraphy of the lower and Coal members of the Copacabana Formation from Apillapampa, central Bolivia was investigated. Twelve samples yielded abundant and diverse, moderately well-preserved pollen and spores. One new spore species, Dictyotriletes cousmineri, is described and 52 species are recorded for the first time in Bolivia. Two species each of acritarchs and scolecodonts are also present. The lowermost assemblage yielded Vittatina and taxa such as Pakhapites ovatus and Marsupipollenites striatus, which are characteristic of the Asselian-Early Artinskian Vittatina costabilis Zone of the Paraná Basin, Brazil. The uppermost assemblage is defined by the appearance of several species of Lueckisporites, together with species of Vittatina, Lunatisporites, Pakhapites, Hamiapollenites, Corisaccites, Mabuitasaccites, Striomonosaccites, Striatoabieites, Striatopodocarpites and Weylandites. Abundant monolete and trilete spores with subordinate pollen grains are present in the Coal Member. Those species suggest correlation to the Middle Artinskian-Wuachiapingian Lueckisporites virkkiae Zone of the Paraná Basin. Highly variable associations of gymnosperms occur in the lower member whereas pteridophytes, sphenophylls and lycopods are dominant in the overlying Coal Member. These groups of plants characterised terrestrial landscapes along marine margins during the Early Cisuralian, and confirm the widespread distribution of the Glossopteris flora during the Permian in Gondwanaland. Preliminary radiometric data from interbedded tuffs suggest an Asselian-Sakmarian age for the marine Copacabana Formation and a Sakmarian-?Artinskian age for the overlying Coal Member. These new data are highly significant in terms of Permian correlations in central South America.